Benefits from constructing a dam across the Vistula in Siarzewo in terms of transport and environmental protection - Kempa, Jan; Chmielewski, Jacek; Bebyn, Grzegorz (International Conference “Environmental Engineering”, 2017)
This paper presents the results of analyses that concern the benefits from the planned construction of a dam across the Vistula in Siarzewo. The simulated transport model developed in the VISUM environment has been used to determine the forecast traffic intensity, the value of traffic volume indices, transport activity, travel times of drivers and passengers as well as the costs of environmental impact. The above-mentioned characteristics have enabled to determine savings both in terms of traffic costs and environmental impacts resulting from the dam construction. The paper indicates that the implementation of the investment project improves traffic conditions on the road network and reduces the transport environmental impact in Kujawsko-Pomorskie Province. Moreover, it has been found that the revealed effects concern in particular the first years after the launch of the project. The development of the road network diminishes the role of the analysed investment project significantly.
Keywords: transport; traffic engineering; environmental impact of road traffic; transport activity; time spent in the network